Frog went a-courtin' - Langstaff, John M.; Rojankovsky, Feodor 1891-1970. (Orlando, Fla. Voyager Books, 1991)
Illustrates the well-known American folk song about the courtship and marriage of the frog and the mouse.
Reprint. Originally published: New York : Harcourt Brace, 1955.
Keywords: Folk songs, English -- England -- Texts; Folk songs